2020
DOI: 10.1123/ijspp.2018-0894
|View full text |Cite
|
Sign up to set email alerts
|

Is the Optimal Load for Maximal Power Output During Hang Power Cleans Submaximal?

Abstract: Purpose: The optimal load for maximal power output during hang power cleans (HPCs) from a mechanical perspective is the 1-repetition-maximum (1RM) load; however, previous research has reported otherwise. The present study thus aimed to investigate the underlying factors that determine optimal load during HPCs. Methods: Eight competitive Olympic weight lifters performed HPCs at 40%, 60%, 70%, 80%, 90%, 95%, and 100% of their 1RM while the ground-reaction force and bar/body kinematics were simultaneously recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Regardless of the loading method, it has been suggested that the JS is best implemented using lighter loads to maximize its speed-strength qualities when compared with other weightlifting derivatives (3,32,36,37). For example, the HPC may maximize power output with moderate-heavy loads (65-90% 1RM) (11,12,30,34,51) whereas peak power outputs during the JS were shown with loads ranging from 30 to 45% 1RM HPC (33,49). Despite these findings, it may be possible to load the JS using heavier loads than the 1RM HPC because of a smaller barbell displacement and the omission of the catch phase.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the loading method, it has been suggested that the JS is best implemented using lighter loads to maximize its speed-strength qualities when compared with other weightlifting derivatives (3,32,36,37). For example, the HPC may maximize power output with moderate-heavy loads (65-90% 1RM) (11,12,30,34,51) whereas peak power outputs during the JS were shown with loads ranging from 30 to 45% 1RM HPC (33,49). Despite these findings, it may be possible to load the JS using heavier loads than the 1RM HPC because of a smaller barbell displacement and the omission of the catch phase.…”
Section: Discussionmentioning
confidence: 99%
“…This opportunity for higher loads permits a greater strength-speed emphasis compared with catching variations, thereby enhancing maximal force and rapid force production (283,288,293,294). On the lower end of the loading spectrum (e.g., 30-60% 1RM), athletes can still maximize their effort because of the ballistic nature of certain pulling derivatives, such as the jump shrug (157,160,284,(298)(299)(300)302) and the hang high pull (157,286,298,299,(302)(303)(304). During the jump shrug and hang high pull, velocity and therefore power output tend to be maximized with loads as low as 30-45% of a hang power clean 1RM (285,298,299,302,304).…”
Section: Section 2: Weightlifting Derivativesmentioning
confidence: 99%
“…The effect of load on the kinetic and kinematic outputs of weightlifting derivatives has been evaluated by numerous researchers (45,48,49,51,53,157,160,195,197,(284)(285)(286)(300)(301)(302)(303)(304). A comparison of exercises and the interaction of load, on force and velocity, is illustrated in Figure 1.…”
Section: Effect Of Exercise and Load On Kinetics And Kinematicsmentioning
confidence: 99%